2021
DOI: 10.1038/s41389-021-00316-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to BET inhibitors in lung adenocarcinoma is mediated by casein kinase phosphorylation of BRD4

Abstract: Targeting the epigenome to modulate gene expression programs driving cancer development has emerged as an exciting avenue for therapeutic intervention. Pharmacological inhibition of the bromodomain and extraterminal (BET) family of chromatin adapter proteins has proven effective in this regard, suppressing growth of diverse cancer types mainly through downregulation of the c-MYC oncogene, and its downstream transcriptional program. While initially effective, resistance to BET inhibitors (BETi) typically occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…In the JQ1-resistant lung adenocarcinoma (LAC) cell line, the phosphorylation of BRD4 was increased, and CK2 was identified as its kinase (63). This suggests that CK2 phosphorylation of BRD4 may be related to the JQ1-resistant lung adenocarcinoma (LAC) cell line (63).…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the JQ1-resistant lung adenocarcinoma (LAC) cell line, the phosphorylation of BRD4 was increased, and CK2 was identified as its kinase (63). This suggests that CK2 phosphorylation of BRD4 may be related to the JQ1-resistant lung adenocarcinoma (LAC) cell line (63).…”
Section: Phosphorylationmentioning
confidence: 99%
“…In the JQ1-resistant lung adenocarcinoma (LAC) cell line, the phosphorylation of BRD4 was increased, and CK2 was identified as its kinase (63). This suggests that CK2 phosphorylation of BRD4 may be related to the JQ1-resistant lung adenocarcinoma (LAC) cell line (63). Further studies showed that JQ1 combined with CK2 inhibitor (CX-4945) could effectively induce the death of lung adenocarcinoma cells and determined the CK2 phosphorylation of BRD4 as a potential target to overcome this cancer resistance (63,64).…”
Section: Phosphorylationmentioning
confidence: 99%
“…Possible mechanisms of resistance to BETis encompass AMPK-ULK1mediated autophagy in AML [76,77], NF-κB in colorectal cancer [78], PP2A phosphatase and BCL2L1/BCL-X in breast cancer [79], the GLI2-dependent Hedgehog pathway in pancreatic cancer [80] and kinome reprogramming in ovarian cancer [81], among others. Further studies demonstrated multiple mechanisms of resistance to BETis in solid tumours, including triple-negative breast cancer (TNBC), CRPC, and lung cancer [82][83][84]. The multitude of resistance mechanisms in diverse cancer models indicates that sensitivity to BETis might be cancer-cell-type-dependent.…”
Section: Resistance To Bet Inhibitorsmentioning
confidence: 99%
“…30,31 The latest study in 2021 suggested that the drug resistance mechanism of BET inhibitors varies with the cancer type, and inhibiting the phosphorylation of BRD4 by casein kinase 2 (CK2) is a potential strategy to overcome drug resistance in cancer patients. 32 CK2 is upregulated in various types of cancers, presenting a vital function in essential biological processes. It is considered as a potential therapeutic target for cancers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…BRD4 inhibitors are capable of inhibiting the transcription of oncogenes in TNBC, serving as promising therapeutic agents. , BRD4 inhibitors have drawn significant attention in recent years. Multiple BET inhibitors have been reported, including JQ1 ( 1 ), I-BET726 ( 2 ), RVX-208 ( 3 ), mivebresib ( 4 ), ZL0516 ( 5 ), ZL0454 ( 6 ), GSK046 ( 7 ), SJ018 ( 8 ), GSK789 ( 9 ), and LT052 ( 10 ) (Figure A), and clinical trials with some BRD4 inhibitors evaluating the therapeutic efficacy against cancers are in progress. ,, A growing number of BRD4 inhibitors have been discovered and applied to the treatment of TNBC, but the emergence of drug resistance was one of the reasons that greatly limited the clinical application. , The latest study in 2021 suggested that the drug resistance mechanism of BET inhibitors varies with the cancer type, and inhibiting the phosphorylation of BRD4 by casein kinase 2 (CK2) is a potential strategy to overcome drug resistance in cancer patients …”
Section: Introductionmentioning
confidence: 99%